REVOLUTIONIZE THE POTENTIAL OF CHATGPT AS TEACHING MATERIAL TO ENGAGE STUDENTS IN LEARNING - Rasjid, A. Ramli; Al Yakin, Ahmad; Muthmainnah, Muthmainnah; Zulfiqar Bin Tahir , Saidna; J. Obaid, Ahmed (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Since ChatGPT was released to the public, several students have used it for academic purposes. This study aimed to investigate the feasibility of implementing ChatGPT as teaching material to motivate students to learn. This study used a survey method through a questionnaire to obtain data. The respondents of this research were the students of the Engineering faculty at Makassar State University, consisting of 77 students. The instrument used was a questionnaire using the Likert scale. Data were analyzed using SPSS version 26. The findings of this study highlighted that most respondents believed that ChatGPT as teaching material impacted students’ motivation to learn Pancasila and citizenship education courses. The implications of this research are to motivate students to learn, and the lecturers should prepare their materials with the appropriate technology, design effective teaching models, and develop curricula and learning activities that can improve comprehensive understanding of the material being taught, the right learning resources, the right technology, and the right teaching instructions. Abstrak: Sejak ChatGPT dirilis ke publik, beberapa mahasiswa telah menggunakannya untuk keperluan akademis. Penelitian ini bertujuan untuk mengetahui kelayakan penerapan ChatGPT sebagai bahan ajar untuk memotivasi siswa belajar. Penelitian ini menggunakan metode survei melalui kuesioner untuk memperoleh data. Responden penelitian ini adalah mahasiswa fakultas Teknik Universitas Negeri Makassar yang berjumlah 77 mahasiswa. Instrumen yang digunakan adalah angket dengan menggunakan skala Likert. Data dianalisis menggunakan SPSS versi 26. Temuan penelitian ini menunjukkan bahwa sebagian besar responden berpendapat bahwa ChatGPT sebagai bahan ajar berdampak pada motivasi siswa mempelajari mata kuliah Pendidikan Pancasila dan Kewarganegaraan. Implikasi dari penelitian ini adalah untuk memotivasi mahasiswa dalam belajar, dan dosen hendaknya menyiapkan materi dengan teknologi tepat guna, merancang model pengajaran yang efektif, dan mengembangkan kurikulum dan kegiatan pembelajaran yang dapat meningkatkan pemahaman komprehensif terhadap materi yang diajarkan, sumber belajar yang tepat, teknologi yang tepat, dan instruksi pengajaran yang tepat.